Sequential treatment for diabetic foot ulcers in aortic dissection patients: a case report - Liang, Huan; Deng, Pin; Yang, Lili; Yuan, Yusong; Ding, Xiaofang (Frontiers in Endocrinology, 2025)
Diabetic foot ulcers (DFUs) represent a prevalent complication of diabetes, with a lifetime risk ranging from 15% to 25% among diabetic patients. Research indicates that anticoagulation plays a crucial role in the management of newly diagnosed cases of diabetic lower extremity atherosclerotic obliterative disease. However, in the present case, the patient developed dry gangrene in both toes after receiving vasodilator drugs during an emergency intervention for sudden aortic dissection. Given that traditional treatments, such as anticoagulation and transfemoral amputation, may not be appropriate for every case, it is imperative to explore alternative therapeutic options. This case report presents pioneering clinical evidence of a tri-therapeutic strategy integrating biomechanical conditioning transverse tibial bone transport (TTBT), Traditional Chinese Medicine Compress Therapy (TCM-CT), and antibiotic-loaded bone cement (ALBC) for diabetic foot ulcer regeneration. This innovative paradigm demonstrates concurrent activation of mechanobiological signaling pathways, phytochemical bioactivity, and sustained antimicrobial protection, achieving complete epithelialization in refractory neuropathic wounds.